Artistic gymnastics as a semiotic construct: the case of the Chinese national team at the Olympic Games - Wang, J.; Yao, D. (Research Square, 2022)
China is one of the most dynamically developing countries that experienced rapid and tumultuous modernization in the second half of the XX century. This modernization consisted of the sports organization improvement and appropriate target-setting in Olympic sports. Sport is the most important sphere of international communication, and gymnastics pertains to the expression of semiotic units by the movement itself. The purpose of this research is to study a semiotic construct embracing the victories, behavior patterns, and organization of the Chinese gymnastics team at the 2008 Olympic Games in Beijing, where China demonstrated its highest achievements in gymnastics. Another reason for selecting these Olympic Games is that semiotically significant elements of the athlete behavior differ from other contexts and Olympics. Consequently, the latter feature facilitates the segregation of these elements through phenomenological research.